Role of Cannabidiol in the Therapeutic Intervention for Substance Use Disorders - Navarrete, Francisco; García-Gutiérrez, María Salud; Gasparyan, Ani; Austrich-Olivares, Amaya; Manzanares, Jorge (Frontiers in Pharmacology, 2021)
Drug treatments available for the management of substance use disorders (SUD) present multiple limitations in efficacy, lack of approved treatments or alarming relapse rates. These facts hamper the clinical outcome and the quality of life of the patients supporting the importance to develop new pharmacological agents. Lately, several reports suggest that cannabidiol (CBD) presents beneficial effects relevant for the management of neurological disorders such as epilepsy, multiple sclerosis, Parkinson’s, or Alzheimer’s diseases. Furthermore, there is a large body of evidence pointing out that CBD improves cognition, neurogenesis and presents anxiolytic, antidepressant, antipsychotic and neuroprotective effects suggesting potential usefulness for the treatment of neuropsychiatric diseases and SUD. Here we review preclinical and clinical reports regarding the effects of CBD on the regulation of the reinforcing, motivational and withdrawal-related effects of different drugs of abuse such as alcohol, opioids (morphine, heroin), cannabinoids, nicotine, and psychostimulants (cocaine, amphetamine). Furthermore, a special section of the review is focused on the neurobiological mechanisms that might be underlying the ‘anti-addictive’ action of CBD through the regulation of dopaminergic, opioidergic, serotonergic, and endocannabinoid systems as well as hippocampal neurogenesis. The multimodal pharmacological profile described for CBD and the specific regulation of addictive behavior-related targets explains, at least in part, its therapeutic effects on the regulation of the reinforcing and motivational properties of different drugs of abuse. Moreover, the remarkable safety profile of CBD, its lack of reinforcing properties and the existence of approved medications containing this compound (Sativex®, Epidiolex®) increased the number of studies suggesting the potential of CBD as a therapeutic intervention for SUD. The rising number of publications with substantial results on the valuable therapeutic innovation of CBD for treating SUD, the undeniable need of new therapeutic agents to improve the clinical outcome of patients with SUD, and the upcoming clinical trials involving CBD endorse the relevance of this review.